Constructing Official Poverty Lines for Countries in Transition – Beyond the Poverty Line (2000-2010) - Marinko Škare; Romina Pržiklas Družeta (Amfiteatru Economic Journal, 2014)
This paper presents a new model for defining the poverty line using the Kakwani (2010) approach and developing a possible candidate for the construction of a new official poverty line. The model uses consumer theory to construct both food and non-food poverty thresholds and ensures that the poverty line is consistent across regions.
Keywords: D31; D63; I31; I32; O57; 330; A new model for constructingpoverty lines; Poverty rates; Calorie cost; Poverty measurement in transition countries